ChemInform Abstract: Tricyclic Fused Pyrazoles with a ′Click′ 1, 2, 3‐Triazole Substituent in Position 3 are Nanomolar CB1 Receptor Ligands. Issue 29 (July 2015) - Zanato, Chiara; Cascio, Maria Grazia; Lazzari, Paolo; Pertwee, Roger; Testa, Andrea; Zanda, Matteo
Abstract Starting from 3‐bromo benzaldehyde, an eleven step synthesis of the substrate (I) is described which is further transformed to the title compounds.